Cover Feature: Rational Design of Dual‐State Emission Luminogens with Solvatochromism by Combining a Partially Shared Donor–Acceptor Pattern and Twisted Structures (Chem. Eur. J. 70/2019). Issue 70 (31st October 2019) - Qiu, Qianqian; Xu, Pengfei; Zhu, Yanjun; Yu, Junru; Wei, Mengru; Xi, Wenbin; Feng, Hui; Chen, Jianrong; Qian, Zhaosheng
Abstract : A general design strategy for dual‐state emission luminogens (DSEgens) with solvatochromism properties was proposed by combining a partially shared donor–acceptor pattern and twisted structures. The DSEgens with bright fluorescence emission in both the solid and solution state demonstrate a unique solvatochromism behaviour depending on solvent polarity and thus may have applications in anti‐counterfeiting. More information can be found in the Communication by Z. Qian et al. on page 15983 .